Effects of Land Application of Farm Dairy Effluent on The Growth of Sweet Corn - Intan Nurcahya; Indra Permana; Erviyana Windiastuti; Rizki Nuralam (Jurnal Biologi Tropis, 2023)
This study investigates the impact of land application of farm dairy effluent (FDE) on the growth and yield of sweet corn (Zea mays var. saccharata). The agricultural sector faces increasing challenges in managing effluents sustainably, and the utilization of FDE as a potential nutrient source for crop production has gained prominence. Field experiments were conducted to assess the effects of FDE application on sweet corn with different rate of irrigation. Randomized completely block design was used an experimental design with different irrigation rate i.e. A = 0% FC effluent, B = 25% FC effluent, C = 50% FC effluent, D = 75% FC effluent, and E = 100% FC. The collected data was analyzed by using ANOVA with 5% of significance, a further test is performed using duncan multiple range test. The results showed that  FDE had TDS, TSS, BOD and COD higher than the standard with values ​​of 1398 mg/L, 2575 mg/L, 3611 mg/L and 6374 mg/L respectively. The application of FDE significantly influenced sweet corn growth especially on height and leaf increment. The application of FDE with 100% FC tends to have higher leaf increment than other treatments at 35 DAA (day after application).